Tinjauan Yuridis Terhadap Retribusi Parkir di Tepi Jalan Umum Dalam Peningkatan Pendapatan Daerah di Kabupaten Semarang - Fajar Asyhari; Adhi Budi Susilo (Rampai Jurnal Hukum (RJH), 2022)
The implementation of Parking Retribution can help to increase Regional Original Income. The local government has made a regulation, namely the Semarang Regency Regional Regulation Number 9 of 2008 concerning Parking Service Fees on the Edge of Public Roads. As a guideline in operationalizing parking levies and providing sanctions for violations and monitoring efforts by the Government. This study uses a sociological empirical method. Collecting data through field studies with interviews and literature studies with analysis of primary, secondary and tertiary legal materials. Sampling, using non-random sampling method with purposive sampling technique. Data analysis used qualitative analysis through the stages of data collection; Data interview; data presentation; and conclusion or verification. The implementation of government administration, namely increasing PAD through public service fees, is not fully in accordance with the Semarang Regency Regional Regulation Number 9 of 2008 concerning Parking Service Fees on the Edge of Public Roads. In this case the researchers found obstacles, namely the lack of internal supervision by the Semarang Regency DPRD, the lack of understanding of the Dishubkominfo in the policy of setting strict sanctions for violators, the lack of personnel in supervising the implementation of the Regional Regulation, the lack of parking levies in increasing Regional Original Income, and the many unofficial jurists operate. The regulation on sanctions is expected to be further emphasized or optimized by the government and the government is expected to optimize the performance of the agencies related to the Semarang Regency Regional Regulation Number 9 of 2008 concerning Parking Service Fees on the Edge of Public Roads. Abstrak           Filsafat Pelaksanaan Retribusi Parkir dapat membantu untuk meningkatkan Pendapatan Asli Daerah. Pemerintah Daerah telah membuat Peraturan yaitu Peraturan Daerah Kabupaten Semarang Nomor 9 Tahun 2008 tentang Retribusi Pelayanan Parkir di Tepi Jalan Umum. Sebagai pedoman dalam mengoperasionalkan retribusi parkir dan pemberian sanksi atas pelanggaran-pelanggaran dan upaya pengawasan oleh Pemerintah. Penelitian ini menggunakan metode empiris sosiologis. Pengumpulan data melalui studi lapangan dengan wawancara dan studi pustaka dengan analisis bahan hukum primer, sekunder dan tersier. Pengambilan sampel, menggunakan metode non-random sampling dengan teknik purposive sampling. Analisis data menggunakan analisis kualitatif melalui tahapan pengumpulan data; Wawancara data; penyajian data; dan kesimpulan atau verifikasi. Implementasi terhadap penyelenggaran pemerintah yakni meningkatkan PAD melelui retribusi jasa umum belum sepenuhnya sesuai dengan Peraturan Daerah Kabupaten Semarang Nomor 9 Tahun 2008 tentang Retribusi Pelayanan Parkir di Tepi Jalan Umum. Dalam hal ini peneliti menemukan hambatan yaitu kurangnya pengawasan internal oleh DPRD Kabupaten Semarang, kurangnya pemahaman Dishubkominfo dalam kebijakan menetapkan sanksi tegas bagi para pelanggar, kurangnya personil dalam pengawasan pelaksanaan Perda, kurangnya retribusi parkir dalam meningkatkan Pendapatan Asli Daerah, dan jukir tidak resmi yang masih banyak beroperasi. Pengaturan atas sanksi diharapkan lebih ditegaskan atau dioptimalkan oleh pihak pemerintah dan Pemerintah diharapkan dapat mengoptimalkan kinerja dari badan-badan yang berkaitan dengan Peraturan Daerah Kabupaten Semarang Nomor 9 Tahun 2008 tentang Retribusi Pelayanan Parkir di Tepi Jalan Umum